2017
DOI: 10.7448/ias.20.1.21748
|View full text |Cite
|
Sign up to set email alerts
|

High risk of loss to follow‐up among South African children on ART during transfer, a retrospective cohort analysis with community tracing

Abstract: Introduction: Decentralization of HIV care for children has been recommended to improve paediatric outcomes by making antiretroviral treatment (ART) more accessible. We documented outcomes of children transferred after initiating ART at a large tertiary hospital in the Eastern Cape of South Africa.Methods: Electronic medical records for all children 0–15 years initiating ART at Dora Nginza Hospital (DNH) in Port Elizabeth, South Africa January 2004 to September 2015 were examined. Records for children transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…2004-Dec. 2012<1 years0.551.5Sidamo [44]Ethiopia20172Public407Jan. 2009-Dec. 2016 < 14 years642.8Teasdale [43]South Africa20171681Jan. 2004-Sept. 2015 < 15 years348.5Vermund [27]Mozambique2014753Jun.…”
Section: Resultsmentioning
confidence: 99%
“…2004-Dec. 2012<1 years0.551.5Sidamo [44]Ethiopia20172Public407Jan. 2009-Dec. 2016 < 14 years642.8Teasdale [43]South Africa20171681Jan. 2004-Sept. 2015 < 15 years348.5Vermund [27]Mozambique2014753Jun.…”
Section: Resultsmentioning
confidence: 99%
“…The Dora Nginza study also failed to identify risk factors for unsuccessful downreferral, but in the study of adolescent transfer in the Western Cape, virological suppression was associated with successful transfer. [15] While documented VL suppression was not associated with retention in care in our study, it would be important to assess this in larger cohorts of similarly aged young children.…”
Section: Discussionmentioning
confidence: 94%
“…In that study, of 644 children receiving ART who were transferred to primary and community health clinics for continuation of care, 33% never arrived at the designated clinic after down-referral. [15] Furthermore, among the 1 582 children initiated on ART during the study period, 53% of all loss to follow-up occurred through unsuccessful down-referral. Finally, by searching the National Health Laboratory Service database, results for 62% (131/211) of those lost to follow-up on down-referral were obtained, and only 5% (10/211) of them were within 18 months of down-referral.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have evaluated the transfer of children and adolescents to alternate clinics to decongest tertiary care facilities in South Africa. Teasdale et al found that only 67% of children successfully transferred and an additional 21% were lost to follow-up after successful transfer [ 34 ]. On the other hand, Ramirez-Avila et al found that 88% of adolescents successfully transferred to government clinics after the closure of a Presidents Emergency Plan for AIDS Relief funded clinic, although notably 48% linked to unintended clinics.…”
Section: Discussionmentioning
confidence: 99%